Biochar application : essential soil microbial ecology - Ralebitso-Senior, T. Komang; Orr, Caroline H.; ScienceDirect eBooks (Amsterdam, Netherlands : Elsevier, 2016)
Biochar Application: Essential Soil Microbial Ecology outlines the cutting-edge research on the interactions of complex microbial populations and their functional, structural, and compositional dynamics, as well as the microbial ecology of biochar application to soil, the use of different phyto-chemical analyses, possibilities for future research, and recommendations for climate change policy. Biochar, or charcoal produced from plant matter and applied to soil, has become increasingly recognized as having the potential to address multiple contemporary concerns, such as agricultural productivity and contaminated ecosystem amelioration, primarily by removing carbon dioxide from the atmosphere and improving soil functions. Biochar Application is the first reference to offer a complete assessment of the various impacts of biochar on soil and ecosystems, and includes chapters analyzing all aspects of biochar technology and application to soil, from ecogenomic analyses and application ratios to nutrient cycling and next generation sequencing. Written by a team of international authors with interdisciplinary knowledge of biochar, this reference will provide a platform where collaborating teams can find a common resource to establish outcomes and identify future research needs throughout the world.
Print version record.
Includes index.
Elsevier
Keywords: Biochar; Soil microbial ecology; SCIENCE -- Life Sciences -- Biology; SCIENCE -- Life Sciences -- Microbiology; Biochar; Soil microbial ecology; Electronic books